2020
DOI: 10.1088/2053-1591/ab69c5
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on tailoring physical properties of Nickel Oxide thin films grown by dc magnetron sputtering

Abstract: We report a comprehensive study on influence of oxygen partial pressure on NiO thin films grown on glass substrates in a combined argon and oxygen ambience by reactive dc magnetron sputtering. In this present article, we have discussed the dependence of oxygen pressure on structural, chemical, morphological, optical and electrical properties of the sputtered NiO films. Glancing angle x-ray diffraction reveals that the deposited films were polycrystalline in nature with FCC phase. The preferred orientation chan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
51
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 157 publications
(70 citation statements)
references
References 44 publications
7
51
0
1
Order By: Relevance
“…In all graphs of Fig. 3, the black dotted ovals indicate the likely experimental range of E VB and N A in NiO x , according to reported values in the literature [41]- [43]. Without including detrimental D it , it appears that standard (p) NiO x with N A of 5 × 10 16 cm −3 and E VB at 5.0 eV is likely not an ideal candidate as a hole-selective contact, since FF and η drop to 27.6% and 8.1%.…”
Section: A Simulated Sensitivity Of Materials Parameterssupporting
confidence: 54%
See 1 more Smart Citation
“…In all graphs of Fig. 3, the black dotted ovals indicate the likely experimental range of E VB and N A in NiO x , according to reported values in the literature [41]- [43]. Without including detrimental D it , it appears that standard (p) NiO x with N A of 5 × 10 16 cm −3 and E VB at 5.0 eV is likely not an ideal candidate as a hole-selective contact, since FF and η drop to 27.6% and 8.1%.…”
Section: A Simulated Sensitivity Of Materials Parameterssupporting
confidence: 54%
“…Namely, we expect E VB,NiO x to shift toward vacuum with increased x and the band gap E G to decrease, as elaborated subsequently. Additionally, it has been reported by numerous studies that increasing O 2 flow during sputter growth reduces resistivity (i.e., increases conductivity) in p-type NiO x [43], [50]- [53]. Some reports indicate an increase in hole doping and decrease in mobility [52], [53], but trends and magnitudes are inconsistent [43], [51].…”
Section: B Case Study: Sputtered P-type Nio X As a Hole-selective Comentioning
confidence: 99%
“…With an increase in the crystallite size, the 2LO and 2TO peak appeared in the spectra of the NiO film grown at 50 W of power. Longitudinal modes LO and 2LO reveal a strong interaction between the nickel and oxygen bonding [24]. In this analysis, we have observed that there is a small shift in the spectra due to the presence of strain in the film, and it is worth noting that the contribution from the glass substrate is also not ruled out.…”
Section: Raman Spectroscopy Analysismentioning
confidence: 76%
“…Therefore, the number of satellite peaks usually arises in the higher BE of the Ni2p 3∕2 , and Ni2p 1∕2 and are dominating due to the mixing of d-d transition and increased Ni3d-O2p hybridization. The separation between the Ni2p 1∕2 , and Ni2p 3∕2 binding energy peak intensity range from 17.39 to 17.40 eV [24,25]. The presence of Ni2p 1∕2 , and Ni2p 3∕2 spectrum binding energy difference is evident of the dependency of the sputter power and reactive oxygen gas on the chemical structure of the grown film.…”
Section: Chemical Analysis (Xps)mentioning
confidence: 97%
“…Similar to n-type materials, p-type metal transparent oxides do not exist widely in nature. Among the available p-type metal oxide thin films, nickel oxide has been given considerable attention due to its p-type conductivity and transparency [8][9][10][11]. A UV detector based on lithium-doped NiO and ZnO was reported by Ohta et al [12].…”
Section: Introductionmentioning
confidence: 99%